Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kayu Jawa (Lannea coromandelica (Houtt.) Merr.) Terhadap Bakteri Penyebab Infeksi Saluran Pencernaan Dengan Metode Difusi Agar - Rabbana, Rahmawati; Kosman, Rachmat; Nuryanti, Siska (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
The purpose of this research was to determine the antibacterial activity of the ethanol extract of Javanwood leaves Lannea coromandelica (Houtt.) Merr.) against bacteria that cause digestive tract infections. The research method begins with the extraction process using the maceration method with 96% ethanol solvent and evaporated using a rotary evaporator. Java wood leaf ethanol extract was subjected to screening tests with a concentration of 0.1%; 0.5%; and 1% against the test bacteria Eschericia coli, Salmonella typhi, Shigella dysenteriae and Vibrio cholerae. MIC and MBC tests were carried out and continued with antibacterial activity tests using the agar diffusion method with variations in concentrations of 0.5%; 1%; 2%; 4%; 8%; and 16%. The results of the screening test for Escherichia coli and Shigella dysenteriae bacteria at 0.5%. MIC values for Escherichia coli bacteria at 0.125% and Shigella dysenteriae bacteria at 2%. While the MBC value for Escherichia coli bacteria is at 0.5% and Shigella dysenteriae bacteria at 2%. The results of testing the antibacterial activity of the ethanol extract of Javanwood leaves against Escherichia coli and Shigella dysenteriae bacteria had the largest diameter of the inhibition zone at a concentration of 16%, respectively 17.10 mm; and 13.56 mm which is included in the criteria of having strong inhibition. Based on the results of the ethanol extract of Javanwood leaves, it has potential as an antibacterial.